Gender identity crisis of the millennial generation in Malaysia: special focus on the issue of Pengkid - Dzulkifli, Mariam Adawiah; Rokis, Rohaiza; Abdul Rahim, Adibah (2018)
Gender identity crisis among Malaysian youth nowadays is becoming a matter of grave concern. This article is based on a study conducted to explore and understand the perception of the public towards Pengkid, a term used to refer to a female, whose physical and behavioural appearance resembles that of a male. The sexual orientation is also towards other females, i.e., showing a preference for same-sex partners. Pengkid is becoming more visible in society and lately, the term has been associated with social concerns, like, drug and sexually-related problems. This study also aims to develop possible indicators for identifying a Pengkid. A combination of quantitative and qualitative research methods is used. A survey was conducted involving a total of 1,298 samples, representing people in three main districts in Negeri Sembilan, i.e., Seremban, Port Dickson and Rembau. Structured interviews were also conducted with several target groups or subject matter experts, such as religious leaders, academicians, lawyers, medical doctors and social workers as well as a number of Pengkid. The main finding from the research indicates that the level of awareness of the public of the Pengkid problem is high. The research also developed some physical and behavioural indicators for the purpose of identifying Pengkid.